PUBLIC ACCOUNTABILITY AND BUDGETARY PARTICIPATION IN THE PUBLIC SECTOR: THE MODERATING ROLE OF BUDGET CLARITY ON MANAGERIAL PERFORMANCE - Widya Wasti Margaretha; Mukhzarudfa; Rita Friyani (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2026)
Managerial performance in the public sector still faces challenges, particularly in budget management, which demands high accountability and broad participation, but often results in suboptimal performance achievements. The study aims to analyze the influence of public accountability, responsibility accounting, and budget participation on managerial performance, with the clarity of budget objectives as a moderating variable. Data analysis was conducted using Moderated Regression Analysis through IBM SPSS Statistics version 25. The study shows that public accountability has a positive and significant effect on managerial performance, while responsibility accounting does not have a significant effect. Budget participation has a negative and significant effect on managerial performance. However, the clarity of budget targets has been proven to moderate this relationship by weakening the influence of public accountability, while simultaneously strengthening the influence of budget participation on managerial performance.